Determination of Nutritional Value and Acceptability of Chicken Nuggets Produced by Chicken Wings and Dehydrated Shellfish - Abd-El-Aziz, Nadia A.; Elsesy, T. A.; Hashem, Saadia M. (Emerging Challenges in Agriculture and Food Science Vol. 4, 2022)
The aim of this study was to utilize the chicken wings in processed chicken nuggets and use shellfish as a source of protein, vitamins and mineral, to produce healthy and economic products. Therefore, the proximate compositions, nutritional value, physical and sensorial properties of these products were evaluated after preparation. The different prepared chicken nuggets supplemented with dehydrated shellfish CN0, CN2, CN4, and CN6 percent. In comparison to the control, there was a significant decrease in moisture and an increase in protein content (p 0.05) in all chicken nuggets (CN). The fat content of CN0 percent was significantly higher than that of CN2 percent, CN4 percent, and CN6 percent. With the addition of dehydrated shellfish, the ash content increased, while the carbohydrate and total calorie content of the different chicken nuggets decreased. TBA values showed no significant difference (p < 0.05) between chicken nuggets. Results showed that using dehydrated shellfish in preparing chicken nuggets caused a marked rise in its content of Ca, Fe, Na, K, Zn, Mg and Mn levels, CN0% had the lowest concentration of all minerals had the lowest concentration of all minerals, and had lower value of vitamins A, E and D but CN6% had higher value of vitamins A, E and D. Control nuggets (CN0%) had the lowest value of yellowness and highest value of lightness but CN6% had highest value of yellowness and, lowest value of lightness. The redness had been reduced slightly. All samples exhibited minor changes in hardness, cohesiveness, springiness, gumminess, and chewiness. The addition of dehydrated shellfish to chicken nuggets resulted in an increase in WHC, pick-up, and cooking loss. Panelists accepted all prepared chicken nuggets, and the chicken nuggets CN4 percent received the highest score when compared to other prepared chicken nuggets.